Learning about animals: viva education: science works for kids series - Moore, Jo Ellen (Viva Education New Delhi, 2004)
This educational book provides an overview of different animal species, their habitats, and behaviors. With vibrant images and interesting facts, it encourages children to explore the animal kingdom and fosters a sense of curiosity about wildlife and conservation.